Integration of cellular network and wireless LAN - Indran, Taruna Kugan; James, Stephen Raj; Satiakumar, Mohishaa; Ishak, Muhammad Isham Fareez; Ismail, Nurul Fatin Athirah; Nathan, Shelena Soosay (Penerbit UTHM, 2021)
This study discusses the significant problems accommodated in the integration of cellular networks and WLANs to the service providers, end-users, etc. This study aims about the current complications, current challenges, substantial significance, future implementations, and the future challenges related to the integration of cellular networks and WLANs. We are performing the research to specifically identify the issues of the integration and how to eliminate these problems to produce a network that delivers higher productivity to users in terms of bandwidth, coverage area, etc. The integration of networks is now in high demand as a diverse range of mobile devices, applications requires the network to be integrated in order to utilize the service anywhere, anytime, and at a reasonable cost. The crucial component in integration is the handoff process that takes place when the user moves from one network to another without experiencing any interruption. Some issues must be considered in all the layers of the protocol stack in order to contribute a breath-taking performance to the end-users who are central to the networks. This study is carried out by referring to past written articles, documents, records, by other researches. This study identifies the problems and issues related to the protocol stack, provides the readers with the importance of integration, and the discussion about this integration of the network.